Análise experimental da eficiência energética de um sistema de refrigeração automatizado utilizando R22 e propileno como fluido refrigerante - Antunes, Arthur Heleno Pontes (2011)
This work contributed to the knowledge about the necessity to replace halogenated fluids by natural refrigerants reducing the damage to the environment. Primarily, it became necessary to know the operation limits of an experimental facility that could be an air conditioning system with maximum refrigerating capacity of 15 kW, operating during summer. At the same time and collectively as the first objective, instrumentation and control strategies were adopted, allowing extending the focus of this research on another topic, energy savings of air conditioning systems. The experimental facility has been submitted at three different configurations: the first one depicted a conventional air conditioning system that, basically, consists of a reciprocating compressor working at nominal frequency, two concentric tubes heat exchanger, a thermostatic expansion valve (TEV) and R22 as refrigerant fluid; in the second case, the compressor speed was controlled by an inverter frequency drive and an electronic expansion valve replaced the TEV; and finally it was proposed a third system configuration, exactly to the second one, in which was used R1270 (propylene) as the working fluid. The results showed that the system operating at frequencies below 60 Hz and the implementation of a PID controller in the mechanism of expansion enabled the improvement in the COP of the automated systems compared to the COP of the conventional system, which used an on-off controller. Consequently, the automation of the conventional system reduced by 35% the average monthly consumption of electricity. The replacement of R22 by R1270 (refrigerant with a smaller GWP) increased even more the values of the COP and reduced the environmental damage, calculated by the total equivalent warming impact (TEWI). It showed that the automation and the replacement of a traditional fluid by a hydrocarbon decrease in 77% the damage to the environment for this specific application.